Hemocompatibility of micropatterned biomaterial surfaces is dependent on topographical feature size - Fallon, Meghan E.; Le, Hillary H.; Bates, Novella M.; Yao, Yuan; Yim, Evelyn K.F.; Hinds, Monica T.; Anderson, Deirdre E.J. (Frontiers in Physiology, 2022)
Small-diameter synthetic vascular grafts that have improved hemocompatibility and patency remain an unmet clinical need due to thrombosis. A surface modification that has potential to attenuate these failure mechanisms while promoting an endothelial layer is the micropatterning of luminal surfaces. Anisotropic features have been shown to downregulate smooth muscle cell proliferation, direct endothelial migration, and attenuate platelet adhesion and activation. However, the effect of micropatterning feature size and orientation relative to whole blood flow has yet to be investigated within a systematic study. In this work, hemocompatibility of micropattern grating sizes of 2, 5, and 10 µm were investigated. The thrombogenicity of the micropattern surface modifications were characterized by quantifying FXIIa activity, fibrin formation, and static platelet adhesion in vitro. Additionally, dynamic platelet attachment and end-point fibrin formation were quantified using an established, flowing whole blood ex vivo non-human primate shunt model without antiplatelet or anticoagulant therapies. We observed a higher trend in platelet attachment and significantly increased fibrin formation for larger features. We then investigated the orientation of 2 µm gratings relative to whole blood flow and found no significant differences between the various orientations for platelet attachment, rate of linear platelet attachment, or end-point fibrin formation. MicroCT analysis of micropatterned grafts was utilized to quantify luminal patency. This work is a significant step in the development of novel synthetic biomaterials with improved understanding of hemocompatibility for use in cardiovascular applications.